FORECAST OF GEOMAGNETIC AND SOLAR ACTIVITY ON NONLOCAL CORRELATIONS - Korotaev S.M.; Serdyuk V.O.; Gorokhov J.V. (My University, 2007)
The article is devoted to the experimental study of the possibility of long-term forecasting of a random component of geomagnetic and solar activity on the base of macroscopic nonlocality effect. The forecasting algorithm, employing the nonlocal correlation detector measurements, is suggested. Its efficiency is proved on data of the long-term experiments in the regime of real forecast simulation with advancement up to four months. All methods employed at present of the forecast of geomagnetic activity operate with its components determined by external factors and its own evolution (even if statistical approaches are used). However, a random (spontaneous) component is rather essential because the forecasted system is complicated in a synergetic sense, the typical feature of which is instability caused by the trajectory divergence in the phase space. It is not very important for the short-term geomagnetic forecast, because the external factors, i.e., the solar activity and interplanetary medium state, are already given by the observations.